2004
DOI: 10.1038/sj.eye.6700731
|View full text |Cite
|
Sign up to set email alerts
|

Open-angle glaucoma and systemic thyroid disease in an older population: The Blue Mountains Eye Study

Abstract: Purpose To assess whether thyroid disease is independently associated with open-angle glaucoma (OAG), using history of thyroid disease and current thyroxine use. Methods The Blue Mountains Eye Study examined 3654 persons, aged 49-97 years. Interviewers collected self-reported history of diagnosis and treatment for thyroid disease. Eye examinations included applanation tonometry, stereoscopic optic disc photography and automated perimetry. OAG was diagnosed from the presence of matching typical glaucomatous fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 36 publications
1
31
1
2
Order By: Relevance
“…A history of thyroid disease was a risk factor for the overall POAG and NTG. This is consistent with a finding of the Blue Mountains study, which showed an association between thyroid disease and POAG [13]. The cited work also found more lower than high-tension glaucoma patients among POAG patients with thyroid disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A history of thyroid disease was a risk factor for the overall POAG and NTG. This is consistent with a finding of the Blue Mountains study, which showed an association between thyroid disease and POAG [13]. The cited work also found more lower than high-tension glaucoma patients among POAG patients with thyroid disease.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated intraocular pressure (IOP), older age [5,6] and African ancestry [2] have been shown to be strongly associated with POAG. A number of other risk factors, including myopia [6,7], a family history of POAG [8,9], a thinner central cornea [9,10], smoking [11] and a history of thyroid disease [12,13], are suggested to be risk factors. However, the studies are not consistent in their findings.…”
Section: Introductionmentioning
confidence: 99%
“…The Blue Mountains prevalence survey found that those with OAG were about twice as likely to be receiving thyroxine treatment or to have had past thyroidectomy. 64 A large database survey found that newly coded OAG patients have 1.4 times the general risk for hypothyroidism. 65 …”
Section: Thyroid Diseasementioning
confidence: 99%
“…Most reports, however, have not found a significant association between thyroid dysfunction and POAG (Table 2). 2,[23][24][25][26][27] No patients were excluded from this audit because of a diagnosis of POAG, nor were any patients treated on ocular anti-hypertensive treatments prior to decompression surgery.…”
Section: Discussionmentioning
confidence: 99%